Screw Anterior Distal Femoral Hemiepiphysiodesis in Children With Cerebral Palsy and Knee Flexion Contractures: A Retrospective Case-control Study. Issue 9 (October 2020) - Long, Jason T.; Laron, Dominique; Garcia, Micah C.; McCarthy, James J.
Abstract : Background: In children with cerebral palsy who demonstrate hamstring tightness, increasing attention is being paid to less invasive methods of correcting knee flexion contractures. Guided growth principles represent one such approach, and in tandem with a serial extension casting protocol, may provide a less invasive method of addressing these contractures. To date, no evidence is available on this combination of procedures. The purpose of this study was to investigate the effectiveness of a combined lengthening/guided growth procedure (hamstring lengthening, percutaneous anterior screw hemiepiphysiodesis, and serial extension casting) in addressing knee flexion contracture, and to compare this approach to hamstring lengthening and serial extension casting alone. Methods: Measures from preoperative and postoperative gait analyses were reviewed retrospectively for 10 patients with cerebral palsy who underwent anterior screw hemiepiphysiodesis and hamstring lengthening followed by serial extension casting [anterior epiphysiodesis (AE) group]. These findings were compared with measures from 19 patients with cerebral palsy who underwent hamstring lengthening followed by serial extension casting [no anterior epiphysiodesis (NAE) group]. Postoperative changes in clinical, functional, and kinematic parameters were assessed. Radiographic parameters were also assessed for the AE group. Results: In the AE group, improvements were measured in knee contracture, popliteal angle, peak stance phase knee extension, knee range of motion, and Gait Deviation Index. Similar results were observed in the NAE group. In the AE group, the lateral distal femoral angle increased into extension by 20.9 degrees at an average of 26-month follow-up. Both groups showed an increase in pelvic tilt postoperatively. There were no surgical complications associated with the screw anterior hemiepiphysiodesis. Four patients did have complaints of knee pain, but the pain was attributable to the implants in only one patient. Discussion: The AE group demonstrated statistically greater postoperative improvement in popliteal angle, knee flexion contracture, and peak knee extension during stance than the NAE group. Both procedures led to improvements in clinical and functional measures, indicating the validity of this approach as a means of correcting flexion contracture that is less invasive and allows immediate weight bearing. Level of Evidence: Level III—therapeutic study.